Osteoprotegerin reduces osteoclast resorption activity without affecting osteogenesis on nanoparticulate mineralized collagen scaffolds - Ren, Xiaoyan (Sci Adv, 2019)
The instructive capabilities of extracellular matrix–inspired materials for osteoprogenitor differentiation have sparked interest in understanding modulation of other cell types within the bone regenerative microenvironment. We previously demonstrated that nanoparticulate mineralized collagen glycosaminoglycan (MC-GAG) scaffolds efficiently induced osteoprogenitor differentiation and bone healing. In this work, we combined adenovirus-mediated delivery of osteoprotegerin (AdOPG), an endogenous anti-osteoclastogenic decoy receptor, in primary human mesenchymal stem cells (hMSCs) with MC-GAG to understand the role of osteoclast inactivation in augmentation of bone regeneration. Simultaneous differentiation of osteoprogenitors on MC-GAG and osteoclast progenitors resulted in bidirectional positive regulation. AdOPG expression did not affect osteogenic differentiation alone. In the presence of both cell types, AdOPG-transduced hMSCs on MC-GAG diminished osteoclast-mediated resorption in direct contact; however, osteoclast-mediated augmentation of osteogenic differentiation was unaffected. Thus, the combination of OPG with MC-GAG may represent a method for uncoupling osteogenic and osteoclastogenic differentiation to augment bone regeneration.